Evaluation and defense of light commands attacks against voice controllable systems in smart cars. (April 2021) - Xu, Zhijian; Zhang, Guoming; Ji, Xiaoyu; Xu, Wenyuan
The in-car voice controllable system has become an almost standard feature in smart cars. Prior work shows that the voice controllable system is vulnerable to light commands attack which uses the laser as the medium to inject voice commands. In this article, we first reproduced the light commands attack on acoustic isolated in-car voice controllable system under several scenarios with a lightweight solution. We validate the feasibility of injecting the malicious voice command through a window into the microphone by modulating a laser beam. Then, we tested a variety of mainstream countermeasures such as placing sunscreen film on the glass panel to see whether it can protect the microphone from being attacked. Surprisingly, we find that the lower light transmittance of sunscreen film is the lower the success rate of the attack. Experiment results also show that when the transmittance rate of sun film is 50% which is the darkest sunscreen film that can be applied, the attacking success rate decreased by up to 0.4. We also explore the impact of attack angle by changing the incidence angle of the laser beam and the results demonstrate that light commands is sensitive to attack angle and the successful angle range is ± 15°. Finally, we propose a series of hardware-based protection schemes against light commands attacks.